Efeitos vasculares do oleorresina de Pterodon spp. Vogel (Fabaceae) e do seu diterpeno isolado (6α-acetoxi-7β-hidroxivouacapano-17β-oato de metila) - Reis, Carolina de Fátima (2015)
The use of medicinal plants for the treatment of hypertension treatment has been extensively studied. The genus Pterodon spp. Vogel (Fabaceae), popularly known as sucupira, has five native Brazilian cerrado species. Studies demonstrated that the Pterodon spp has antispasmodic and myorelaxant activities. Phytochemical studies of sucupira found furanic diterpenes with vouacapanic skeleton in their fruits, and the therapeutics activities from this gender are essentially attributed to these compounds. The aim of this study was to evaluete the possible vasorelaxant activity and the mechanisms of action of the oil-resin of sucupira (SOR) and its isolated diterpene, methyl-6α-acetoxy-7β-hydroxyvouacapan-17β-oate in isolated rat aorta preparations. For comparison, verapamil curves (1 nM – 100 μM) were also obtained. The results demonstrated that both, S0R (0 – 56 μg/mL) and the isolated diterpene (0 – 48 μg/mL) have a reversible concentration-dependent vasorrelaxant activity. Endothelium denudation did not impair in the relaxant effect of both, ORS and the diterpene. Aortic rings KCl-stimulated obtained a lower IC50 value than rings contracted with phenylephrine under increasing concentrations of the tested substances. The SOR and diterpene relaxant activity was not impaired when nonselective K+ channels blockers were used (Tetraethylammonium). The use of cyclopiazonic acid (SERCA inhibitor) indicated that there was no involvement of the Ca2+ reuptake by sarcoplasmatic reticulum and the use of ODQ (an inhibitor of guanylyl cyclase) and MDL-12,330A (an inhibitor of adenylyl cyclase), showed that the 3, 5- cyclic guanosine monophosphate (cGMP) and 3',5'-cyclic adenosine monophosphate (cAMP) pathways were not involved in SOR relaxant activity. However, the results indicate a possibly activity of the soluble guanylyl ciclase on diterpene relaxant effect. Both, SOR and isolated diterpene inhibited the CaCl2 induced contractions in aortic rings stimulated with phenylephrine (0.1μM) or Bay K8644 (a Cav1.2 channel activator; 1μM) and by depolarizing KCl solution (40 mM). Computational molecular docking studies demonstrated that the vasodilator effect of diterpene relies on blocking the Cav1.2 channel, and patch clamp results showed that diterpene substantially decreased the ionic current through Cav1.2 in freshly dissociated vascular smooth muscle cells. These findings suggest that SOR and its isolated diterpene induce endothelium-independent vascular relaxation by blocking the L-type Ca2+ channel (Cav1.2).